VIRTUAL PREVIEW MODULE DEVELOPMENT WITH A SKILL APPROACH APPLICATION ASSISTED SCIENCE PROCES SELECTRIC CIRCUIT STUDIO (ECSTUDIO) OF DYNAMIC ELECTRICAL MATTER - Nur Hasanah; Wawan Bunawan (UNIVERSITAS NEGERI MEDAN, 2021)
The research aims to design a virtual preview module with a scientific process skill approach with a dynamic electrical circuit application on electric matter. This research method uses descriptive research methods with quantitative approaches, on ADDIE development models with the sat analysis stages (data and information collection), design (product planning), early product development, implementation (initial field test), evaluation (revision of test results). The research subject is a virtual preview module with a scientific process skill approach. The object of research is dynamic electrical matter. The product developed was validated by 6 validator experts made up of 3 validator experts, 3 validator media experts. Also seen the response of two physics teachers. Initial field trials were carried out by passing an engagement sheet to 8 students. Research shows that virtual preview modules with a scientific process skill approach with a dynamic electrical circuit application on the electric circuit studios are declared worthy after validation by materials experts, media experts, teachers and student responses. Assessment of material experts with an average percentage of 81.93% in valid/ worthy categories, media with an average percentage of 85.92% in valid/ worthy category, teacher response rate 86.33 % with dancing really well and an 80.32% with the attractive category and the final trial in the large class obtained a percentage of 85.11% with the very interesting categor